Revitalisasi dan Pemekaran Kota Lama di Tanjung Pinang - Wiky Dwipa Abial; Aulia Agustin; Mellyana Candra (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The revitalization and expansion plan for the old city in Tanjung Pinang aims to renew and expand the area by considering population growth, infrastructure needs and preserving historical values. Revitalization may involve restoring historic buildings, improving infrastructure, developing commercial or cultural zones, and improving the environment.Expansion of an old city can include expanding administrative areas, establishing special areas that maintain cultural authenticity, as well as developing public spaces for social and economic activities. Apart from that, this plan needs to consider the participation of the local community in order to meet needs and maintain the unique identity of Tanjung Pinang.Regarding this plan, it is important to consider various aspects such as cultural preservation, sustainable development, good spatial planning, as well as active involvement from the government and community.